A Novel Asymmetric Hybrid-Layer Del-Shaped Rotor Interior Permanent Magnet Motor for Electric Vehicles - Mathus Suphama; Pattasad Seangwong; Nuwantha Fernando; Jonggrist Jongudomkarn; Apirat Siritaratiwat; Pirat Khunkitti (IEEE Access, 2024)
Interior permanent magnet (IPM) motors have garnered widespread popularity in electric vehicle (EV) applications due to their distinctive advantages, including superior torque density, high efficiency, and a wide speed range. In this work, the asymmetric hybrid-layer del-shaped ( $\nabla $ -shaped) IPM motor is introduced to enhance the torque capability of the benchmark IPM motor designed for EVs. The proposed motor incorporated an asymmetric PM configuration, integrating hybrid-layer PMs arranged in a $\nabla $ -shaped pattern. To achieve the design objectives, the initial motor design was optimized using a Genetic algorithm, considering sensitivity analysis to precisely attain the targeted torque capability based on EV-specific objective functions. Subsequently, the electromagnetic performance of the proposed motor was analyzed through finite element analysis, and a comparison was made with a symmetric IPM benchmark structure. The results clearly demonstrate the superiority of the proposed asymmetric IPM motor, which exhibits significantly higher average torque, attributed to the effective utilization of the magnetic field shifting effect. Furthermore, a notable reduction in torque ripple was revealed, with this motor experiencing only 9.62% torque ripple, rendering it a suitable choice for EV applications. Additionally, enhanced magnet utilization resulting from the asymmetric permanent magnet configuration in the proposed motor was observed. The overall efficiency of the asymmetric IPM motor was enhanced, reaching an impressive 96.68%. Consequently, the proposed asymmetric IPM motor represents an eminently practical and efficient solution for EV applications.